2007
DOI: 10.1039/b700676b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and oxidation of ethanol on colloid-based Pt/C, PtRu/C and Pt3Sn/C catalysts: In situ FTIR spectroscopy and on-line DEMS studies

Abstract: The interaction of colloid-based, carbon supported Pt/C (40 wt%), PtRu/C (45 wt%) and Pt3Sn/C (24 wt%) catalysts with ethanol and their performance for ethanol electrooxidation were investigated in model studies by electrochemical, in situ infrared spectroscopy and on-line differential electrochemical mass spectrometry measurements. The combined application of in situ spectroscopic techniques on realistic catalysts and under realistic reaction (DEMS, IR) and transport conditions (DEMS) yields new insight on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(171 citation statements)
references
References 54 publications
4
161
0
6
Order By: Relevance
“…4 Under-potential-deposited (upd) H(ads) should also be a reaction-blocking adsorbate up to around 0.1 V, as has been suggested by Behm and coworkers 9 There is a large literature on upd H(ads) on platinum surfaces. A recent theoretical study using calculated Gibbs energies was able to accurately reproduce the cyclic voltammogram for Pt(111) in acid and found that at 0.1 V the H(ads) coverage was ∼ 1 2 ML.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…4 Under-potential-deposited (upd) H(ads) should also be a reaction-blocking adsorbate up to around 0.1 V, as has been suggested by Behm and coworkers 9 There is a large literature on upd H(ads) on platinum surfaces. A recent theoretical study using calculated Gibbs energies was able to accurately reproduce the cyclic voltammogram for Pt(111) in acid and found that at 0.1 V the H(ads) coverage was ∼ 1 2 ML.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to the above, there have been numerous other investigations that have given additional insight into the details and complexities of ethanol electrooxidation on platinum [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and some of them are comparative studies of platinum and platinum alloys, 6,7,9,11,13,14,[17][18][19] and a few study temperature dependencies of the electrooxidation. 6,7,16 Findings in several of these studies will be discussed later in this paper.…”
mentioning
confidence: 99%
“…Five milligrams of the catalyst was dispersed in a mixture of 2 mL water, 2 mL ethanol, and 50 L Nafion solution ͑5 wt %, Aldrich͒ with ultrasonic stirring to form a homogeneous ink. 19 The catalyst layer was prepared by dropping 20 L of the ink onto a GC disk electrode by a microsyringe and drying at room temperature. All potential values in this paper are referred to a reversible hydrogen electrode.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 According to CO stripping voltammetry results, the PtSnO 2 /C catalyst presented a much negative shift in the onset potential compared with the PtRu/C catalyst; however, the oxidation current on the PtRu/C catalyst increased more rapidly with potential than that on the PtSnO 2 /C catalyst, suggesting that Ru is more effective than SnO 2 in promoting CO ads electro-oxidation at relatively high potentials. 18,19 For the ternary PtRuSn/C catalyst previously reported, Sn is mainly present in the oxidized state on the catalyst surface, and the improvement in the catalytic activity for methanol electro-oxidation is usually ascribed to the synergistic effect of SnO 2 and Ru species. 10 However, the catalytic activity of the PtRuSn/C catalyst is also reported to be inferior to that of the PtRu/C catalyst because SnO 2 that covers with Pt sites blocks the adsorption of methanol and is detrimental to the catalytic activity.…”
mentioning
confidence: 99%
“…This means that H ads is expected to block ethanol oxidation when the electrode is at potentials below 0.1 V. Blocking was observed by Behm and coworkers. 18 Therefore, for potentials above 0.1 V, up to about 0.6 V, reactions such as 1a and 2a may be allowed over unblocked sites, provided the activation energies are low enough.…”
Section: R-h Oxidation In the Under-potential Deposited (Upd)mentioning
confidence: 99%